Thyroid tissue in cervical lymph nodes, not always malignant. Issue 9 (6th September 2022) - Gijsen, Anton Frans; De Bruijn, Kirstin Marie Jeanne; Mastboom, Walter
Abstract: Thyroid tissue in cervical lymph nodes is an interesting and rare phenomenon that cannot be directly explained by embryology. Distinguishing malignant from benign thyroid tissue in cervical lymph nodes can be challenging but is essential for treatment and might have legal implications. Patients with incidentally found thyroid tissue in cervical lymph nodes during thyroid surgery were retrospectively identified. Clinical data and findings on pathology were retrospectively collected. Two patients with thyroid tissue in cervical lymph nodes were identified. Conventional pathology complemented with immunohistochemistry and molecular diagnostics showed the thyroid tissue in cervical lymph nodes to be benign. We show that benign thyroid tissue in cervical lymph nodes can be found in the absence or presence of a primary thyroid malignancy. A conservative approach is recommended if pathology shows benign thyroid tissue in cervical lymph nodes. Abstract : Thyroid tissue in cervical lymph nodes can be found in the abcence or presence of a primary thyroid malignany. A conservative approach is recomended if pathology shows benign thyroid tissue in cervical lymph nodes.